PULMONARY NOCARDIOSIS IN A PATIENT WITH DIABETES MELLITUS - Yasin, Mohammad; Mumtaz Muhammad,; Aziz Ahmad,; Shamsurrahman,; Faheem Jan, (Journal of Ayub Medical College Abbottabad, 2022)
Nocardiosis is considered as one of the rare systemic infections. It is usually prevalent in immunocompromised individuals though few cases have been reported in immunocompetent individuals as well. With the advent of new microbiological classifications and increasing progress in laboratory technology this infection is being diagnosed more frequently. Hence it is important to diagnose and treat this disease timely in order to reduce its associated morbidity and mortality. Nocardiosis is a rare condition and is often overlooked. Hence this case is presented.